DUAL TA’LIM SIFATINI OSHIRISHDA AXBOROT-TA’LIM MUHITINI SHAKLLANTIRISH - Siddiqova, S.G‘. (SCIENCE and SOCIETY, 2025)
This article discusses improving the quality of dual education through the formation of an information-educational environment and the use of information-educational resources. The article emphasizes the importance of effectively utilizing information educational resources to improve education quality. It offers recommendations for educators and educational institutions on integrating information technologies into the educational process.
Keywords: dual education; quality of education; information environment; resource; electronic